Effect of grain coalescence on the abnormal grain growth of Pb(Mg1/3Nb2/3)O-3-35 mol% PbTiO3 ceramics - Chung, UJ; Park, JK; Hwang, NM; Lee, HY; Kim, DY (WILEY, 2002)
Abnormal grain growth (AGG), which occurred during the heat treatment of Pb(Mg1/3Nb2/3)O-3-35 mol% PbTiO3 (PMN-35PT) with excess PbO, was investigated. AGG has been suggested to be the consequence of grain coalescence that results in the formation of Sigma3 coincidence site lattice and low angle grain boundaries. Because of reentrant edges appearing at the ends of these boundaries, the coarsening rate of grains was significantly enhanced and AGG occurred.
Keywords: SINGLE-CRYSTALS; COARSENING BEHAVIOR; LIQUID; TEMPERATURE; DEPENDENCE; SHAPE